Weathering, Frost Action, and Patterned Ground in the Mesters Vig District, Northeast Greenland. - Washburn, A. L. (Meddelelser om Grønland, 1969)
Chemical weathering is locally important in the Mesters Vig district as proved by observations on oxidation, on solution and deposition of calcium carbonate, and on desert varnish, case hardening, exfoliation, cavernous weathering, granular disintegration, and development of Arctic Brown soil. Hydration is probably the most widespread and effective of the chemical processes, although its weathering effect involves physical prying. Aside from scattered prying by roots of woody plants such as Betula and Salix at generally low altitudes, frost wedging is probably the only widespread purely physical weathering process operating. That frost wedging breaks up rock more rapidly in the Mesters Vig environment than in more temperate climates having frost action is not demonstrated; the striking prevalance of physical weathering effects may merely reflect a strong dominance of physical over chemical weathering. Frost action comprises a number of processes. Frost cracking has probably formed certain polygonal features. Frost heaving is widespread and very important; among other phenomena, it accounts for raised joint blocks in bedrock and for upfreezing of stones and other objects in mineral soil. Based in part on data from a number of experimental sites, both the "frost pull" and the "frost push" hypotheses of upfreezing of objects are regarded as valid. Mass displacement-the en-masse local transfer of mobile mineral soil from one place to another within the soil as the result of frost action-is demonstrably an important process but its exact nature is not established; cryostatic pressure may be a factor but changes in density and intergranular pressure are regarded as probably more important. A number of these frost-action processes produce sorting effects. Permafrost is widespread, and pingos are common along some drainages. Patterned ground is common in moist locations. Both small and large nonsorted and sorted patterns are present but large nonsorted polygons and some large sorted nets are apparently less active than formerly. Based on the review of frost-action processes and on the field evidence, a genetic grouping of the forms is suggested. For specific occurrences at Mesters Vig, the basic processes are probably (1) desiccation cracking for most small nonsorted polygons, some small nonsorted stripes, and, in combination with one or more sorting processes, for small sorted polygons; (2) frost cracking for large nonsorted polygons, large nonsorted stripes, and, in combination with one or more sorting processes, for large sorted polygons; (3) dilation cracking for some small nonsorted polygons; (4) sedimentation for some nonsorted circles and related forms; (5) mass displacement for most nonsorted circles and related forms, debris islands, large sorted nets, some turf hummocks (in part), and, in combination with gelifluction, for most large sorted stripes; (6) rillwork for some small nonsorted stripes and the small sorted stripes; (7) differential mass-wasting for some large sorted stripes; (8) frost wedging (and frost heaving) for some other large sorted stripes. Further research may well modify some of the conclusions, but the Mesters Vig observations strongly support the polygenetic origin of many similar, as well as dissimilar, forms of patterned ground.